2020
DOI: 10.21873/invivo.11998
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features in Elderly ALK-rearranged Non-small Cell Lung Cancer Patients

Abstract: Aim: To clarify the clinicopathological features in elderly anaplastic lymphoma kinase (ALK) rearranged non-small cell lung cancer (NSCLC) patients. Patients and Methods: A retrospective study was performed in 129 ALK rearranged NSCLC patients diagnosed between April 2008 and March 2019 in fifteen Institutions of the Ibaraki prefecture, Japan. Results: Median age of patients was 63 years. In 59 patients aged 65 and older, the proportions of patients with advanced stage and those treated with ALKtyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[ 12 ] However, a number of elderly-onset ALK mutations have been reported. [ 13 ] In studies of patients with ALK-positive lung cancer, the proportion of elderly patients (≥65 years old) was reported to be 10% to 20% [ 14 ] while some studies showed a higher proportion (36–46%). [ 13 ] There has only been one reported case of ALK-positive adenocarcinoma in a patient with RA but without OP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] However, a number of elderly-onset ALK mutations have been reported. [ 13 ] In studies of patients with ALK-positive lung cancer, the proportion of elderly patients (≥65 years old) was reported to be 10% to 20% [ 14 ] while some studies showed a higher proportion (36–46%). [ 13 ] There has only been one reported case of ALK-positive adenocarcinoma in a patient with RA but without OP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] In studies of patients with ALK-positive lung cancer, the proportion of elderly patients (≥65 years old) was reported to be 10% to 20% [ 14 ] while some studies showed a higher proportion (36–46%). [ 13 ] There has only been one reported case of ALK-positive adenocarcinoma in a patient with RA but without OP. [ 15 ] The relationship between ALK mutations and RA with OP remains unknown, and chronic inflammation may contribute to the development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%